2015
DOI: 10.1007/s00191-015-0405-9
|View full text |Cite
|
Sign up to set email alerts
|

Equity dynamics in bargaining without information exchange

Abstract: In this paper, completely uncoupled dynamics for n-player bargaining are proposed that mirror key behavioral elements of early bargaining and aspiration adjustment models (Zeuthen 1930, Sauermann & Selten 1962. Individual adjustment dynamics are based on directional learning adjustments, solely driven by histories of own realized payoffs. Bargaining this way, all possible splits have positive probability in the stationary distribution of the process, but players will split the pie almost equally most of the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Applied to cooperative games, the key property of these dynamics is for coalitions to rearrange if they make some players better‐off (and noone worse off), which dynamically mirrors the ‘blocking argument’ of the core counterfactual. We have studied dynamics that are similar to the ones we consider here in a series of related papers (Nax, ; Nax, ; Nax and Pradelski, ; Nax and Pradelski, ) . In these papers, it is shown that these dynamics implement the core and select equitable core outcomes within the core (of assignment games Nax and Pradelski (), of many‐to‐one matching Nax and Pradelski (), and of multi‐player bargaining Nax ()).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Applied to cooperative games, the key property of these dynamics is for coalitions to rearrange if they make some players better‐off (and noone worse off), which dynamically mirrors the ‘blocking argument’ of the core counterfactual. We have studied dynamics that are similar to the ones we consider here in a series of related papers (Nax, ; Nax, ; Nax and Pradelski, ; Nax and Pradelski, ) . In these papers, it is shown that these dynamics implement the core and select equitable core outcomes within the core (of assignment games Nax and Pradelski (), of many‐to‐one matching Nax and Pradelski (), and of multi‐player bargaining Nax ()).…”
Section: Introductionmentioning
confidence: 93%
“…We have studied dynamics that are similar to the ones we consider here in a series of related papers (Nax, ; Nax, ; Nax and Pradelski, ; Nax and Pradelski, ) . In these papers, it is shown that these dynamics implement the core and select equitable core outcomes within the core (of assignment games Nax and Pradelski (), of many‐to‐one matching Nax and Pradelski (), and of multi‐player bargaining Nax ()). The contribution of this note is to study core implementation for general, superadditive transferable‐utility cooperative games in characteristic function form.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…3 In particular, Nax and Pradelski (2015) use a learning rule based on aspiration adaptation (Sauermann and Selten, 1962;Selten, 1998) which found extensive support in laboratory experiments (Tietz and Weber, 1972;Tietz et al, 1978;Scholz et al, 1983). Aspiration-based learning rules were subsequently used by Nax (2015), Pradelski (2015), and Hamza and Shamma (2017) and form the basis for our proposed effectively convergent dynamic.…”
Section: Related Literaturementioning
confidence: 99%
“…not in every case we observe that the larger the group, the lower the contribution. Finally, there are also some works that explain the level of contribution as a reinforcement learning process (Nax and Perc (2015), Nax (2015)). For an exhaustive review on the different elements that are able to influence the contribution to the public good see Perc et al (2013).…”
Section: Introductionmentioning
confidence: 99%